Influence of left ventricular unloading on pediatric post-cardiotomy veno-arterial extracorporeal life support outcomes - Meani, Paolo; Lorusso, Roberto; Kowalewski, Mariusz; Isgrò, Giuseppe; Cazzaniga, Anna; Satriano, Angela; Ascari, Alice; Bernardinetti, Mattia; Cotza, Mauro; Marchese, Giuseppe; Ciotti, Erika; Kandil, Hassan; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background The effectiveness of veno-arterial extracorporeal life support (V-A ECLS) in treating neonatal and pediatric patients with complex congenital heart disease (CHD) and requiring cardio-circulatory assistance is well-known. Nevertheless, the influence of left ventricle (LV) distension and its countermeasure, namely LV unloading, on survival and clinical outcomes in neonates and children treated with V-A ECLS needs still to be addressed. Therefore, the aim of this study was to determine the effects of LV unloading on in-hospital survival and complications in neonates and children treated with V-A ECLS. Methods The clinical outcomes of 90 pediatric patients with CHD under 16 years of age supported with V-A ECLS for post-cardiotomy cardiogenic shock (CS) were retrospectively reviewed in relationship with the presence or absence of an active LV unloading strategy. Results The patient cohort included 90 patients (age 19.6 ± 31.54 months, 64.4% males), 42 of whom were vented with different techniques (38 with atrial septostomy (AS) or left atria cannula, two with cannula from LV apex, 1 with intra-aortic balloon pump (IABP), and one with pigtail across the aortic valve). The LV unloading strategy significantly increased the in-hospital survival (odds ratio [OR] = 2.74, 95% CI 1.06–7.08; p = 0.037). On the contrary, extracorporeal cardiopulmonary resuscitation decreased the related survival (OR = 0.32, 95% CI 1.09–0.96; p = 0.041). The most common complications were infections (28.8%), neurological injury (26%), and bleeding (25.6%). However, these did not differently occur in venting and no-venting groups. Conclusion In pediatric patients with CHD supported with V-A ECLS for post-cardiotomy CS, the LV unloading strategy was associated with increased survival.